The Role of School Principal in Implementing Education Quality Management - Susana Siti Riani; Siti Quratul Ain (Jurnal Ilmiah Sekolah Dasar, 2022)
Education is one of the most important factors in human life. With education, a person can improve intelligence and skills and develop their potential in humans. The principal's role is very influential in improving the quality of education. Principals must be able to foster and direct teachers to work together and professionally to improve the quality of students To improve the quality of education. This study aims to analyze the role of school principals in improving education quality management at the elementary school level. This study uses a qualitative approach with a descriptive method. The research subjects were one principal and two fourth and fifth-grade teachers. Then, the data collection techniques used were interviews, observation, and documentation. Analyzing the data is done by collecting information through interviews, data reduction, and data presentation. The study results found that the principal has carried out the role of the principal following his role as Manager, Leader, Supervisor, Administrator, Educator, Innovator, and Motivator. The principal has also made efforts to improve the quality of students and is trying to realize the school's vision and mission, realizing active, effective, and efficient learning, as well as producing good learning characteristics and students' moral values.